Which anti-TNF is most effective for my patient? Which one should I choose? - Pamukcu, Melih; Aydogan Baykara, Rabia (Journal of Surgery and Medicine, 2021)
Background/Aim: Multicenter controlled studies were conducted on the effect of anti-Tumor Necrosis Factor (TNF) agents in rheumatoid arthritis (RA) and varying effectiveness rates were reported. These agents have different advantages over each other. We aimed to compare the disease activation parameters in patients with RA at the beginning and the 52nd week of therapy in patients who were followed up in our center and started on anti-TNF (etanercept, adalimumab, and golimumab), and examine the effects of the drugs that are used by comparing them with each other. Methods: This retrospective cohort study included 187 patients with RA who were started on anti-TNF therapy because the disease activity could not be controlled by the concomitant use of at least three different conventional Disease-Modifying Anti-Rheumatic drugs, and whose adequate response to anti-TNF were observed at the 12th-week follow-up. RA disease activity was measured using the 28-joint Disease Activity Score incorporating erythrocyte sedimentation rate (DAS-28 ESR) and the patients were evaluated by a Health Assessment Questionnaire (HAQ). For each drug group, disease activation and laboratory parameters were compared before treatment initiation and at 52 weeks of treatment. These values were then compared between the drug groups. Results: The mean age of 187 patients included in the study was 52.70 (10.17) years, 119 (63.6%) were female and 68 (36.4%) were male. Of the patients, 63 (33.7%) were using adalimumab, 62 (33.2%) were using etanercept and 62 (33.2%) were using golimumab. In all patients, there was a significant improvement in all parameters except mean corpuscular hemoglobin, gamma-glutamyl transferase, and creatinine. There were significant changes in hemoglobin, leukocyte and platelet count, erythrocyte sedimentation rate, C reactive protein, neutrophil count, serum albumin, DAS-28 ESR, and HAQ levels in all three groups (P<0.05). Conclusion: There were no differences in efficacy between adalimumab, etanercept and golimumab therapies, which were planned considering the comorbidities and drug preferences of the patients. In addition to controlled studies, real-life data to be reported by rheumatology centers will help us obtain more accurate information about the therapy results of anti-TNF agents.